Optimasi Daur Ulang Sampah untuk Meningkatkan Kreativitas dan Potensi Penjualan Produk Ramah Lingkungan di Kuripan - Baiq Dinda Puspita Ayu; Ika Putri Fitri Ajiani; Qatrunnada; Khairunnisa; Istin Fitriana Aziza (LPPI UMN AL WASHLIYAH, 2025)
The increasing amount of improperly managed waste, especially plastic waste, has become a pressing environmental issue in many communities, including at SDN 1 Kuripan. This community service program aims to raise students' awareness about sustainable waste management and enhance their creativity in recycling waste into eco-friendly products. The program also seeks to provide understanding regarding the importance of waste separation and the harmful impacts of waste on the environment. The community service was conducted on Tuesday, December 2 and 4, 2025, from 08:30 AM to 04:00 PM, consisting of socialization, recycling training, and the creation of eco-friendly products such as bags made from plastic waste and pencil cases from used cardboard. Additionally, the program concluded with an exhibition of students' works aimed at raising awareness within the surrounding community. The results showed that students successfully improved their understanding of the importance of waste management and demonstrated creativity in producing useful recycled products. The exhibition also successfully attracted the attention of the community, increasing their awareness about waste management. This program has a positive impact on environmental education and the empowerment of the economy through waste recycling.